A Multivariate‐Gated DNA Nanodevice for Spatioselective Imaging of Pro‐metastatic Targets in Extracellular Microenvironment. Issue 4 (2nd December 2021) - Xiang, Zhichu; Zhao, Jian; Qu, Junle; Song, Jun; Li, Lele
Abstract: Probing pro‐metastatic biomarkers is of significant importance to evaluate the risk of tumor metastasis, but spatially selective imaging of such targets in extracellular microenvironment is particularly challenging. By introducing the bilinguality of PNA/peptide hybrid that can speak both peptide substrate and nucleobase‐pairing languages to combine with aptamer technology, we designed a smart DNA nanodevice programmed to respond sequentially to dual pro‐metastatic targets, MMP2/9 and ATP, in extracellular tumor microenvironment (TME). The DNA nanodevice is established based on the combination of an ATP‐responsive aptamer sensor and a MMP2/9‐hydrolyzable PNA/peptide copolymer with a cell membrane‐anchoring aptamer module. Taking 4T1 xenograft as a highly aggressive tumor model, the robustness of the DNA nanodevice in spatioselective imaging of MMP2/9 and ATP in TME is demonstrated. We envision that this design will enable the simultaneous visualization of multiple pro‐metastatic biomarkers, which allows to gain insights into their pathological roles in tumor metastasis. Abstract : A multivariate‐gated DNA nanodevice was engineered for spatially selective, correlated imaging of ATP and MMP2/9 in extracellular tumor microenviroment. The simultaneous visualization of the dual pro‐metastatic biomarkers may allow to discriminate tumors with high risk of metastasis.